Migration Timing and Wintering Areas of Three Species of Flycatchers (Tyrannus) Breeding in the Great Plains of North America - Jahn, Alex E. (2013)
Descriptions of intra- and interspecific variation in migratory patterns of closely related species are rare yet valuable because they can help assess how differences in ecology and life-history strategies drive the evolution of migration. We report data on timing and location of migration routes and wintering areas, and on migratory speed and phenology, of Eastern Kingbirds (Tyrannus tyrannus) from Nebraska and Oklahoma and of Western Kingbirds (T. verticalis) and Scissor-tailed Flycatchers (T. forficatus) from Oklahoma. Eastern Kingbirds primarily departed the breeding site in September, migrating to the Amazon Basin (Bolivia and Brazil), >6,400 km from their breeding site, then used a second wintering site in northwestern South America (Colombia, Ecuador, and Peru) before returning to the breeding site in April. Western Kingbirds left Oklahoma in late July, migrating >1,400 km to northwestern Mexico, then to central Mexico and finally to Central America before returning to Oklahoma in April. Scissor-tailed Flycatchers departed Oklahoma mainly in mid-October, migrating to Central America (El Salvador, Guatemala, Honduras, and Nicaragua), ∼2,600 km from the breeding site, remaining there until early April before returning to Oklahoma. Timing of migration appears to be tightly linked to molt. Early departure of Western Kingbirds from the breeding site appears to be timed so that they molt in the Sonoran Desert region during the monsoon, whereas Scissor-tailed Flycatchers remain at their breeding site to complete molt in late summer, when insect prey are abundant. Eastern Kingbirds delay molt until reaching South America where, possibly, abundant fruit supports molt.